Molecular characterisation of congenital glaucoma in a consanguineous Canadian community: a step towards preventing glaucoma related blindness. Issue 6 (1st June 2000) - Martin, S Nicole; Sutherland, Joanne; Levin, Alex V; Klose, Robert; Priston, Megan; Héon, Elise
Abstract : Glaucoma is a leading cause of irreversible blindness in Canada. Congenital glaucoma usually manifests during the first years of life and is characterised by severe visual loss and autosomal recessive inheritance. Two disease loci, on chromosomes 1p36 and 2p21, have been associated with various forms of congenital glaucoma. A branch of a large six generation family from a consanguineous Amish community in south western Ontario was affected with congenital glaucoma and was studied by linkage and mutational analysis to identify the glaucoma related genetic defects. Linkage analysis using the MLINK component of the LINKAGE package (v 5.1) showed evidence of linkage to the 2p21 region (Zmax=3.34, θ=0, D2S1348 and D2S1346). Mutational analysis of the primary candidate gene, CYP1B1, was done by direct cycle sequencing, dideoxy fingerprinting analysis, and fragment analysis. Two different disease causing mutations in exon 3, 1410del13 and 1505G→A, both segregated with the disease phenotype. The two different combinations of these alleles appeared to result in a variable expressivity of the phenotype. The compound heterozygote appeared to have a milder phenotype when compared to the homozygotes for the 13 bp deletion. The congenital glaucoma phenotype for this large inbred Amish family is the result of mutations in CYP1B1 (2p21). The molecular information derived from this study will be used to help identify carriers of the CYP1B1 mutation in this community and optimise the management of those at risk of developing glaucoma.